2022
DOI: 10.3390/ijerph19106189
|View full text |Cite
|
Sign up to set email alerts
|

Can Emotion Regulation Affect Aggressive Responses? A Study on the Ukrainian–Russian Conflict in a Non-Directly Exposed Sample

Abstract: On 24 February, Russian President Vladimir Putin gave the order to invade neighbouring Ukraine; a typical trend during the war is considering events in a one-sided way, emphasising the exclusive contribution of one opponent over the other for the outbreak of war. War may trigger the experience of emotions, such as anger, shame, and disgust. The present study reproduces previous studies on the influence of emotional regulation in support of aggressive reactions (AR) in the Israeli–Palestinian conflict. A questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Active hostility exerts a severe impact not just on the population of sides of the conflict. A wave of mental health consequences of the current Russian war in Ukraine in non-directly exposed populations has also been reported in other countries [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Active hostility exerts a severe impact not just on the population of sides of the conflict. A wave of mental health consequences of the current Russian war in Ukraine in non-directly exposed populations has also been reported in other countries [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, the relationship between addictions and the regulation/dysregulation of emotions shown to play an important role both in war and peace times in other conflicts [ 21 ] should be considered for tailored interventions since adaptive emotional regulation strategies decrease the experience of negative emotions [ 11 ]. In particular, the Italian study on the role of emotion regulation on aggressive responses related to the current Russian–Ukrainian conflict has shown the negative effect of cognitive reappraisal of emotions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our data suggest that vulnerable populations, including victims of the armed conflict, present high levels of arousal and aggression, which research has shown are predictors of personal injuries or homicides (Meloy, 2000). Accordingly, the development of psychosocial programs with a strong emotion regulation training component seems needed (e.g., Bruneau et al, 2022; Cricenti et al, 2022; Hurtado-Parrado et al, 2019). Additionally, our results suggest that perspective taking (i.e., cognitive empathy) correlates with reductions in aggression, at least when arousal is low.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individuals with high level of shame‐proneness may be more involved in the behavior of aggression and NSSI. Researchers indicated that aggression in response to shame may be viewed as emotion regulation (Cricenti et al, 2022; Elison et al, 2014; Wang & Sang, 2020). Similarly, as mindfulness has been shown to be associated with emotion regulation, shame‐proneness may play a mediating role in the association between mindfulness and aggression and NSSI.…”
Section: Discussionmentioning
confidence: 99%